Consumer Awareness and Behavioural Trends in the Adoption of Millets and Millet-based Products - , Manpreet Kaur; , Gagandeep Banga (Archives of Current Research International, 2025)
The study aims to investigate the consumer awareness and buying behavior towards millets and millets-based products in Ludhiana city. A descriptive research design was used to guide data collection and analysis. The primary data was collected through a structured and non-disguised questionnaire. A total sample of 200 respondents was selected for the study based on convenience sampling. The findings indicated that in terms of awareness, 78% of respondents were familiar with pearl millet (Bajra), followed by 72% with sorghum (Jowar), and 54.5% with finger millet (Ragi). Awareness was significantly lower for other millets, including Foxtail (Kangni), Kodo, and Little Millet. The study found that 80% of respondents purchase millet flour, followed by millet cookies (56%) and breakfast cereals (35%). A majority (66%) spend less than Rs. 700 monthly on millet products, with only 8% spending over Rs. 1000. Social media (57%) and word of mouth (48%) were the primary sources of information. Most respondents (30%) buy millet products once a month, while 21% buy occasionally. Grocery/kirana stores (53%) were the most common purchase location, followed by supermarkets (39%). The findings suggest a need for more affordable and accessible millet-based products and increased consumer awareness.